Limited additional value of dual-layer spectral 4DCT compared with conventional 4DCT for preoperative localization in primary hyperparathyroidism - Jorian P. Krol; Tessa Veerbeek; Laura N. Deden; Frank B.M. Joosten; Marie Louise E. Bernsen; Cornelis H. Slump; Wim J.G. Oyen (European Journal of Radiology Open)
Purpose: Primary hyperparathyroidism, characterized by excessive parathyroid hormone secretion, is typically caused by solitary parathyroid adenomas or multiglandular disease. Accurate preoperative localization is critical for successful surgical parathyroidectomy. While four-dimensional CT (4DCT) is commonly used for this purpose, spectral-CT techniques have recently been introduced, offering improved tissue differentiation. Rapid kV switching and dual-source spectral-CT have been studied, however, this is the first study that evaluates the effectiveness of dual-layer-CT in preoperatively locating parathyroid adenomas in a larger population. Approach: From April 2020 to October 2023, patients with confirmed primary hyperparathyroidism underwent dual-layer spectral 4DCT before surgery. Spectral reconstructions (MonoE40keV, Iodine-Density, Z-effective, Iodine-no-Water, Virtual Non-Contrast) were analyzed alongside conventional CT reconstructions. Mean attenuation values were compared using one-way ANOVA. ROC curves with paired-sample analysis assessed the ability of different reconstructions to distinguish between thyroid and parathyroid tissue, and lymph nodes and parathyroid tissue. Results: Thirty-six patients with thirty-nine parathyroid adenomas were analyzed. Conventional CT reconstructions demonstrated significantly higher AUC values for differentiating thyroid from parathyroid tissue across all phases compared to spectral reconstructions (0.83–0.95 vs. 0.65–0.89, p-value 0.007-<0.001). No significant difference was found between conventional and spectral reconstructions in distinguishing lymph nodes from parathyroid tissue (0.64–0.96 vs. 0.58–0.96, p-value 0.070–0.957). Virtual non-contrast (VNC) reconstructions showed smaller attenuation differences and lower AUC values in arterial and delayed phases compared to true non-contrast (p = 0.031 and 0.034). Conclusions: Dual-layer spectral-CT is comparable or inferior to conventional CT in tissue differentiation. VNC reconstructions are not recommended as a substitute for true non-contrast due to inconsistent results. In this cohort, dual-layer spectral 4DCT did not demonstrate clear clinical advantage; further validation is warranted.